Literature Review: The Effect of Interpersonal Communication on Service Quality in Hospitals: Literatur Review: Pengaruh Komunikasi Interpersonal antara Tenaga Medis dengan Pasien terhadap Kualitas Pelayananan di Rumah Sakit - Jayanti, Hardani Dwi (Politeknik Harapan Bangsa Surakarta, 2022)
Effective interpersonal communication between the hospital and the patient will provide maximum service quality results. This business will also have a positive impact. The quality of hospital services is not solely related to the completeness of medical equipment, but also relates to interpersonal communication between the hospital and the patient that is well established so that it will give satisfaction to the patient. In addition, it will also have the effect of healing and treating patients' illnesses which in principle depend on interpersonal communication in the form of advice, input, and empathy given by the medical team to bring to the patient. So that interpersonal communication is very influential on the quality of hospital services. The purpose of this study was to determine the effect of interpersonal communication on the quality of service in hospitals. The method used in this study is a literature review, where researchers use methods to be able to identify and review, evaluate and interpret previous research. The results showed that interpersonal communication has a positive impact on the quality of service in hospitals. The majority of people who use hospital services will also consider the interpersonal communication that exists between patients and hospitals, this is also related to the comfort provided by hospitals to patients.